A Service Quality of Islamic Microfinance Institutions in Indonesia: An Importance-Performance Analysis Approach - Dety Nurfadilah; Sudarmawan Samidi; Iwan Kurniawan Subagja (Institute for Research and Community Empowerment (LPPM TAZKIA), 2018)
The rapid growth of financial system in Indonesia creates an intensive competition between Conventional and Islamic financial institutions. The study aims to evaluate the service quality of Islamic Microfinance Institution in Indonesia. The survey was carried out to acquire data from 126 respondents. Descriptive statistics and importance performance analysis (IPA) was used to analyze the data. The finding show that attributes plotted in quadrant “keep up the good work” are providing prompt service, and helpful response to customer requests, Ability in providing services to the customer as needed, prompt service on financial counselling, Ability of staff in giving proper explanation to the customer, Ability to keep the transaction process secure, and Sharia compliance banking products. Meanwhile, the attributes plotted in quadrant “concentrate here” are accessible of location of ATM, easy to access the location, ability to navigate customer to find what they intend, ability to maintain accuracy of bank statement, and ability in providing after sale services. To the best of author’s knowledge, it is the first study that measuring the service quality of Islamic microfinance from customer perspective using importance-performance approach.